Monoclonal Gammopathy of Undetermined Significance with Amyloid Deposition in the Lung and Non-Amyloid Eosinophilic Deposition in the Brain: A Case Report - Francois Abi-Fadel; Nisarg R. Desai; Gita Vatandoust; Rabih Said; Aaron Gottesman; Terenig Terjanian (Case Reports in Medicine)
Background. Monoclonal gammopathy of undetermined significance (MGUS) is rarely complicated by amyloidosis. Case. A 66-year-old white male presented to the emergency room (ER) after an unwitnessed fall and change in mental status. Patient was awake and alert but not oriented. There was no focal deficit on neurological exam. Past medical history (PMH) included hypertension, hypercholesterolemia, aortic valve replacement (nonmetallic), incomplete heart block controlled by a pacemaker and IgG- IgA type Monoclonal Gammopathy of Undetermined Significance. The MGUS was diagnosed 9 months ago on serum protein electrophoresis (SPEP) as patient was referred to the outpatient clinic for hyperglobulinemia on routine blood work. In ER, a head-computed tomography (CT) revealed multiple parenchymal hemorrhagic lesions suspicious for metastases. A CT chest, abdomen and pelvis revealed numerous ground-glass and solid nodules in the lungs. Lower extremity duplex and transesophageal echocardiogram were negative. Serial blood cultures and serologies for cryptococcus and histoplasmosis, antineutrophil cytoplasmic antibody (ANCA), antinuclear antibody (ANA), rheumatoid factor (RF), cryoglobulin, and antiglomerular basement membrane (anti-GBM) antibodies were all negative. CT guided lung biopsy was positive for Thioflavin T amyloid deposits. Brain biopsy was positive for eosinophilic material (similar to the lungs) but negative for Thioflavin T stain. The patient's clinical status continued to deteriorate with cold cyanotic fingers developing on day 12 and a health care acquired pneumonia, respiratory failure, and fungemia on day 18. On day 29, family withdrew life support and denied any autopsies. Conclusion. Described is an atypical course of MGUS complicated by amyloidosis of the lung and nonamyloid eosinophilic deposition in the brain. As MGUS might be complicated by diseases such as amyloidosis and multiple myeloma, a scheduled follow-up of these patients is always necessary. Further research is needed in order to better define the optimal treatment and management strategies of MGUS and its complications.